Boosting the capacitance and voltage of aqueous supercapacitors via redox charge contribution from both electrode and electrolyte. (August 2017) - Hwang, Jee Y.; El-Kady, Maher F.; Li, Mengping; Lin, Cheng-Wei; Kowal, Matthew; Han, Xu; Kaner, Richard B.
Graphical abstract: Highlights: Simple laser technique is used for the direct writing of high-energy supercapacitors. The electrode design involves 3D graphene scaffold doped with Fe3 O4 nanoparticles. The addition of a redox electrolyte increases the voltage window and capacitance. The key is designing both electrode and electrolyte to store charge simultaneously. The technique allows for printing multiple microscale supercapacitors at the same time. Abstract: Supercapacitors are evolving into an important component in energy storage technology with the capability for storing and discharging energy very quickly and effectively. State-of-the-art supercapacitors feature activated carbon electrodes impregnated with a non-aqueous electrolyte (typically acetonitrile) that operate at voltages between 2.2–2.7 V. Unfortunately, activated carbons have low specific capacitance (100–120 F g −1 ) in organic electrolytes which severely limits the energy density of supercapacitors. In addition, organic solvents are often flammable leading to safety and environmental concerns. Aqueous electrolytes, on the other hand, are safer, cheaper and have higher ionic conductivity, promising higher capacitance electrodes. However, the low voltage window enforced by the low decomposition voltage of water around 1.23 V is a major challenge. Here, we demonstrate symmetric supercapacitors operating at an ultrahigh voltage of 1.8 V that can provide specific electrode capacitances up to 716 F g −1, which is higher than traditional activated carbon electrodes. This is possible through designing both the electrode and electrolyte to work synergistically towards improving not only the capacitance of the electrodes, but also the voltage and cycling stability of the supercapacitor. We also demonstrate by using a simple laser technique the possibility of fabricating micro-supercapacitors with great potential for miniaturized electronics. This work provides an effective strategy for designing and fabricating aqueous supercapacitors that hold promise for a sustainable energy future.